Optimal configuration strategy of energy storage considering flexible response of high energy-consuming industrial and mining loads in independent microgrid - Yixi, Cuomu; Liu, Xiaoming; Li, Yu; Tan, Jingming; Liu, Zhihong; Danzeng, Basang; Wang, Lei (Frontiers in Energy Research, 2025)
The coordinated optimization of industrial and mining loads with energy storage (ES) is a critical approach to achieving power and energy balance in microgrids while promoting the new energy accommodation. Addressing the issue of insufficient flexibility in demand response from high-energy-consuming lithium mining loads, which may lead to conservative ES capacity allocation and underutilization of complementary flexibility potential, this paper proposes an ES optimization strategy for microgrids considering the participation of high-energy-consuming lithium mining loads in demand response. Firstly, considering the production process of extracting lithium from salt lakes brine and the electricity consumption characteristics of major energy-consuming equipment, a mathematical model is developed to quantify the flexibility adjustment potential of lithium mining loads under production behavior constraints. Based on this, incorporating the regulation boundaries of photovoltaic (PV) units, gas turbine units, concentrated solar power (CSP), ES system, and flexible lithium mining loads, an ES capacity optimization model is constructed to minimize the comprehensive system capital and operation costs in independent microgrid. The model is then linearized into a mixed-integer programming problem. Finally, through case study simulations of an actual microgrid in Southwest China, the feasibility and effectiveness of the proposed ES optimization strategy are verified. The results demonstrate that the proposed strategy can economically and effectively meet the power and energy balance of the independent microgrid and the electricity demands of high-energy-consuming loads, while promoting the improvement of new energy accommodation capacity.